Keputusan Konsumen dalam Pembelian Sayuran Hidroponik di Kota Bandar Lampung City - Berliana MS, Juwita; Apriyani, Marlinda; Desfaryani, Rini; Budi Trisnanto, Teguh (Journal of Food System & Agribusiness, 2024)
The increasing rate of population growth can cause the need for food to increase for survival. In society, a healthy lifestyle is a standard measure of quality. A healthy lifestyle can be started by consuming healthy foods such as hydroponic vegetables which are free from pesticides and other chemicals. This research aimed to analyze the factors that influence purchasing decisions. This decision making process uses Accidental Sampling using the virtucio formula if the population is difficult to know, using descriptive analysis tools, and logistic regression with a total of 100 respondents. Based on the first consumer decision making process, namely Search,  Evaluation of alternatives, Purchase decision, Post-purchase. Based on the results  of the analysis, there are factors that influence purchasing decisions; there are 2 factors that have a partially significant effect and have a positive influence on purchasing decisions about pandan fragrant rice, namely the taste, quality and quality variables, while the price and packaging variables do not have a significant effect on the decision of the purchase.